Knowledge networks to support youth engagement in sustainable food systems - Huambachano, Mariaelena; Arulingam, Indika; Bowness, Evan; Korzenszky, Anna; Mungai, Catherine; Termine, Paola; Wittman, Hannah (Frontiers in Sustainable Food Systems, 2022)
Young people are on the front lines of transforming agriculture and food systems, coping with the social and economic impacts of COVID-19 as well as environmental and climate change effects which are likely to accelerate and intensify during their lifetimes. At the same time, young people across global contexts are increasingly emerging as visible agents of change in food systems, especially through networks that create, transform, and distribute food systems knowledge. This policy and practice review examines the role of youth as actors through food systems knowledge networks. Increasing youth participation in creating sustainable food systems for the future requires policies and practices that support food systems-related knowledge in two ways: (1) democratizing formal education systems; and (2) strengthening horizontal networks of grassroots research and innovation, including through traditional, ecological, local and community knowledge (TELCK). Food systems policies should be developed through dialogue with diverse knowledge systems, experiences, place-based needs, and aspirations of young people to maximize their participation in food systems policy development and evaluation.